KOMPOSISI HASIL TANGKAPAN PUKAT PAYANG YANG DIDARATKAN DI PPI UJONG BAROH KABUPATEN ACEH BARAT - Hafinuddin Hafinuddin; Ainul Mardian; Taufiq Taufiq (Universitas Teuku Umar, 2017)
The potential of strategic fish resources in Ace Barat District is especially pelagic fish species andit catch is usingboat seine (payang). The aims of this study is to know the type of fish, the number of fish and the composition of the fish species caught using boat seine in the Zone of Potensial Fishingof West Aceh District. This research was conducted in January to February 2016 at Ujong Baroh FishLanding Johan Pahlawan Sub-district, West Aceh District. Survey and purposive sampling method are method used to collect data on the composition of fishermen boat seine. Descriptive analysis was used to analysis data. The results show that there were 5 species of fish caught using boat seine, namely kelang trieng (Caesio cuning), turok (Alepes kalla), meuneng (Sardinella sirn), tambal (Hypoatherina valencienne) and kembung (Restralliger sp). The number of catch fish that used as the sample is 124 individuals. Based on the catch frequency, Sardinella sirnfish and Alepes kalla fish species are more dominant than the others fish, which is 3 times of trips (75%) of the totalof trips (4 times). However, based on the quantity of the catch, Sardinella sirn fish has a larger number of 41 individuals with details male 20 individuals and females 21 individuals. Based on the frequency and quantity of catches, it is assumed that in January and February is the fishing season of Sardinella sirn fish in the waters of West Aceh District